Geospatial organization of regional landscape parks of Poltava region as objects of recreational and tourist activities - Shukanova, Anzhela; Shukanov, Pavlo; Vishnikina, Liubov; Yermakov, Vyacheslav; Sarnavskyi, Serhii (Human Geography Journal, 2025)
Regional landscape parks (RLP) as multifunctional objects of the nature reserve fund combine the functions of nature protection, environmental education and recreation, are key objects of recreational and tourist activities. The purpose of the study is the scientific justification and analysis of the geospatial organization of regional landscape parks of the Poltava region from the standpoint of their use as objects of recreational and tourist activities. Five regional landscape parks have been established in the territory of the Poltava region, which, according to physical parameters and scales of activity, can be divided into: 1) macro-RLPs, focused on the preservation of large river-valley systems -Nyzhnevorsklaynskyi, Hadyatskyi and Dykanskyi; 2) meso-RLPs - Kremenchuksky Plavni; 3) micro-RLPs, to which RLP Kagamlytskyi belongs. The functional zoning of the Kagamlytskyi and Nyzhnyovorsklyanskyi RLPs is closest to scientifically based recommendations. The least proportional distribution of functional zones is in the Hadyatskyi RLP, which has the smallest relative area of the protected zone (3%) and the largest economic area (92.6%). The Kremenchuksky Plavni RLP has the largest area of the protected zone (64.4%): it is dominated by the nature conservation function with the corresponding development of educational and scientific tourism. For the Dykanskyi and Hadyatskyi RLPs, in which the share of the economic zone is disproportionately high, it is advisable to specialize in rural (agro-) and cultural and educational tourism. A unique specialization of recreational and tourist activities for the Nyzhnyovorsklyanskyi and Kremenchuksky Plavni recreational and tourist activities may be ornithological and water tourism after the lifting of martial law restrictions. The common leading type of recreational and tourist activities for all RLPs of the Poltava region is ecotourism and active types of tourism - hiking and cycling.